Enhanced photocatalytic efficiencies of TiO2 nanoparticles loaded with WO3 and Pt for exhaust decomposition. (31st October 2018) - Hu, Dongliang; Li, Rui; Li, Mingming; Pei, Jianzhong; Zhou, Bochao; Guo, Fucheng
Abstract: TiO2, WO3 /TiO2 and Pt/WO3 /TiO2 hybrid nanoparticles were prepared to measure the photocatalytic decomposition efficiencies on hydrocarbons (HC), nitrogen oxides (NOx ) and carbon monoxide (CO), for the purpose to produce pavement coatings that can clean up vehicle exhaust. X-ray diffraction (XRD), scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR) and UV-Vis-NIR spectrophotometer were used to characterize the nanoparticles. The decomposition rates of exhaust after 60 min photocatalytic reactions under UV and visible light irradiation were recorded to calculate the decomposition efficiencies. The optimum WO3 content in WO3 /TiO2 binary nanoparticles is 2 atomic% (at%), and the optimum Pt content in Pt/WO3 /TiO2 ternary nanoparticles is 1 at%. The decomposition efficiencies of WO3 /TiO2 are higher than that of TiO2 but lower than Pt/WO3 /TiO2 both under UV and visible light irradiations. Meanwhile, the decomposition efficiencies of all the photocatalysts under visible light are lower than that under UV light. By analyzing the experimental results, the loading of WO3 is proved to be more effective in decomposing HC, NOx and CO under visible light compared to the loading of Pt. Under UV light irradiation, the WO3 addition contributes more to the decompositions of HC and NOx, while the Pt addition contributes more to the decomposition of CO.